Coordinated control for Air Handling Unit and Variable Air Volume boxes in multi-zone HVAC system. (November 2021) - Ma, Shunjian; Zou, Yuanyuan; Li, Shaoyuan
Abstract: In this paper, a coordinated strategy of distributed model predictive control (DMPC) is proposed to accommodate Air Handling Unit (AHU) and Variable Air Volume boxes (VAV boxes) in a multi-zone HVAC (Heating Ventilation and Air Conditioning) system. A modified distributed model predictive control with equivalent local cooling cost and a total-air-mass-rate penalty term is implemented to local VAV boxes to regulate indoor temperature. The penalty term and AHU supply air temperature are updated in the upper coordinated layer to guarantee the total air mass rate within the limit and economic operation. In this framework, with the help of coordination from both DMPC and the upper layer, the operational cost from the HVAC system can be reduced. The effectiveness of the proposed scheme is proved by a numerical simulation. Highlights: A coordinated DMPC is proposed to accommodate equipment in multi-zone HVAC system. A modified DMPC is implemented to regulate indoor temperature. The coordinated layer is used to keep the total air mass rate within the limit. The supply air temperature PID generates a suitable value for subsystems.